"Hot Lung" Sign in Pulmonary Intravascular Large B-Cell Lymphoma on 18F-FDG PET/CT. (April 2020) - Şahin, Özlem; Kaya, Buğra; Serdengeçti, Mustafa; Çizmecioğlu, Hilal Akay; Şen, Ahmet Eren
Abstract : Abstract: Intravascular large B-cell lymphoma is a rare type of non-Hodgkin lymphoma characterized by intravascular proliferation of clonal lymphocytes within the lumen of small vessels, which is often fatal. Diffuse FDG uptake in the lung without clear/evident CT findings, "hot lung, " is quasi-pathognomonic for lung intravascular large B-cell lymphoma. In this report, we present the case of a 43-year-old man who was diagnosed as having intravascular lymphoma thanks to this rare finding.